Analysis of the Physicochemical Burden of Oyo State Fish Pond, Ibadan, Southwest Nigeria - BB Babatunde; GN Woke (Journal of Applied Sciences and Environmental Management)
Physicochemical characteristics of the Oyo State fish pond (OYSFP) was analysed to assess the water quality status in relation to the fish produced in the pond for human consumption. The pond was originally designed to control storm waters from the high lands around but was later converted for the purpose of commercial fish production and other uses by the State Government. The pond is a recipient of tributaries of wastewaters from Premier Hotel (PHWW), Coca Cola bottling plant (CCWW), University of Ibadan Teaching Hospital (UCHWW) and Bodija Residential area (BDJWW). Results of the physico-chemical parameters showed most of the parameters were higher than the maximum permissible limits for surface waters and discharge of wastewaters into surface waters. Premier Hotel wastewater (PHWW) had the lowest pH value of 6.41 and the most acidic of all the wastewaters sampled. OYSFP recorded the lowest dissolved oxygen value of 2.03mg/L and the highest BOD, COD, nitrate, TS and conductivity values of 78.04mg/L, 235.26mg/L, 78 mg/L, 1428.50, 947μS/cm respectively. The highest sulphate value of 248 mg/L was recorded for BDJSW, this was probably due to runoffs from vegetable gardens along the stream bearing inorganic fertilizers. Other macroscopic observations showed that PHWW was slimy to touch, fowl smelling, dark in colour and had animal life forms such as maggots and flying insects residing in it. CCWW was brownish in colour and slightly smelly and fishes were sighted. OYSFP was dark, muddy, fowl smelling, the surface was covered by aquatic weeds predominantly water hyacinth. UCHWW was transparent, foamy, slimy, slightly smelly and no animal life was sighted in it. BDJWW was clear, no odour, animal life forms including fish and surface arthropods were sighted. Results of physicochemical parameters reported in the present study indicate contamination in OYSFP and fish produced there may not be suitable for human consumption.